MODEL PEMANFAATAN CERITA RAKYAT DALAM PENGEMBANGAN LITERASI BUDAYA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Rina Sapro'ah; Devi Afriyuni Yonanda; Ari Yanto; Ani Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine and synthesize a model for utilizing folktales in developing cultural literacy among elementary school students through a Systematic Literature Review (SLR) approach. The study is grounded in the need to strengthen cultural literacy amid globalization, which may erode students’ local identity. The method follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including identification, screening, eligibility, and inclusion stages of scholarly articles published between 2020 and 2025 from various academic databases. A total of 15 selected articles were analyzed using content analysis and thematic synthesis techniques. The findings indicate that the use of folktales in learning can be conceptualized into three main components: cultural content, instructional strategies, and cultural literacy outcomes. Instructional strategies are classified into three categories: exploratory, reflective, and applicative, which systematically support the internalization of cultural values. This model results in three dimensions of cultural literacy: cultural knowledge, literacy skills, and cultural disposition. These findings highlight that folktales serve as an integrative, contextual, and effective learning medium in fostering cultural literacy among elementary school students. This study contributes to the development of a conceptual model of culturally responsive learning applicable to primary education.